Anti-diabetes and anti-obesity medicinal plants and phytochemicals : safety, efficacy, and action mechanisms /: safety, efficacy, and action mechanisms. (2017) - Saad, Bashar; Zaid, Hilal; Shanak, Siba; Kadan, Sleman
No abstract available